2017
DOI: 10.5539/gjhs.v9n10p174
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Medical Survey among School Teachers in Jeddah, Saudi Arabia

Abstract: The study aims to evaluate the awareness level regarding the importance of medical survey among a sample of school teachers in public and the private sectors. The study has investigated the presence of Otolaryngologic diseases including Dysphonia among teachers. A cross-sectional sample was selected from different parts of Jeddah city to enroll the elementary, intermediate, and the high school teachers. There were more than 800 schools; however, the study has selected 26 schools only. The study was conducted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In (figure 6) when asked the participants if they knew about craniofacial anomalies 51.11% of the participants knew about craniofacial anomalies ( represented in red ) and the rest of the participants that is 48.89% said that they are not aware of craniofacial anomalies ( represented in blue ). The present research work was elicited from works done by investigators, where previous studies were done based on clinical reports, interventional studies like 20,21 ,in vitro studies like 15,[17][18][19][22][23][24][25] , and systematic reviews, 14,26,27,28 .According to previous Similar study all predoctoral dental undergraduate students showed learning diagnosis, treatment,awareness on craniofacial surgery and similar to our study. In (fi gure.10) When asked the participants if they are aware of craniofacial surgeons are being treated the same as MBBS doctors 50.37%( represented in red ) said no that they are not being treated in the same way and the rest of the participants that is 49.63% (represented in blue )said that they are being treated in the same way.…”
Section: Resultsmentioning
confidence: 54%
“…In (figure 6) when asked the participants if they knew about craniofacial anomalies 51.11% of the participants knew about craniofacial anomalies ( represented in red ) and the rest of the participants that is 48.89% said that they are not aware of craniofacial anomalies ( represented in blue ). The present research work was elicited from works done by investigators, where previous studies were done based on clinical reports, interventional studies like 20,21 ,in vitro studies like 15,[17][18][19][22][23][24][25] , and systematic reviews, 14,26,27,28 .According to previous Similar study all predoctoral dental undergraduate students showed learning diagnosis, treatment,awareness on craniofacial surgery and similar to our study. In (fi gure.10) When asked the participants if they are aware of craniofacial surgeons are being treated the same as MBBS doctors 50.37%( represented in red ) said no that they are not being treated in the same way and the rest of the participants that is 49.63% (represented in blue )said that they are being treated in the same way.…”
Section: Resultsmentioning
confidence: 54%